Zero frequency zonal flow excitation by energetic electron driven beta-induced Alfvén eigenmode. (20th August 2020) - Qiu, Zhiyong; Chen, Liu; Zonca, Fulvio; Ma, Ruirui
Abstract: Zero frequency zonal flow (ZFZF) excitation by trapped energetic electron driven beta-induced Alfvén eigenmode (eBAE) is investigated using non-linear gyrokinetic theory. It is found that, resonant energetic electrons (EEs) not only effectively drive eBAE unstable, but also contribute to the non-linear coupling, leading to ZFZF excitation. The trapped EE contribution to ZFZF generation is dominated by EE responses to eBAE in the ideal region, and is comparable to thermal plasma contribution to Reynolds and Maxwell stresses.